2021
DOI: 10.3389/fpubh.2021.622762
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Status of General Population in Hubei Province During the COVID-19 Outbreak: A Cross-Sectional Survey Study

Abstract: Introduction: The current outbreak of the novel coronavirus disease 2019 (COVID-19), originating from Wuhan (Hubei, China), has rapidly spread across China and several other countries. During the outbreak of COVID-19, mental health of the general population in Hubei province may be affected. This study aimed to assess the psychological status and associated risk factors of the general population in Hubei province during the COVID-19 outbreak.Methods: A cross-sectional online survey was used to evaluate the sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…Based on the hypothesized mediation model, one of the major findings was that 6-month follow-up levels of emotional competence played a vital mediating role in the association between 6-month follow-up depression and COVID-19 exposure after controlling for gender, age, and ethnicity. Most prior studies on mental health in the COVID-19 preferred to explore its correlation between outcome variables without including potential mediators of psychological disorders (44,45). The results from the current study suggested that emotional ability related variables, particularly the ones examining the levels of emotional skills or capabilities, could be included when exploring long-term psychological disorders in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 85%
“…Based on the hypothesized mediation model, one of the major findings was that 6-month follow-up levels of emotional competence played a vital mediating role in the association between 6-month follow-up depression and COVID-19 exposure after controlling for gender, age, and ethnicity. Most prior studies on mental health in the COVID-19 preferred to explore its correlation between outcome variables without including potential mediators of psychological disorders (44,45). The results from the current study suggested that emotional ability related variables, particularly the ones examining the levels of emotional skills or capabilities, could be included when exploring long-term psychological disorders in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 85%
“…Around 46% of the participants had stress levels above the cut-off (score = 24 on IES-R), with a Mean score = 22.9 (SD = 14.9) (see Table 7 ), which goes with previous studies that also used IES-R to measure stress levels in the Chinese context during the pandemic. For Chen et al ( 106 ) and Ting et al ( 113 ) the considerable stress percentage was 44.5% for sample's N = 9,225 (Median is provided = 16.0) and 45.2% (Mean score = 26.61; SD = 17.95), respectively. However, our sample's PTSD mean was lower than that of studies conducted in 2020 [e.g., see, ( 15 )], which may consistent with a longitudinal study by Wang et al ( 16 ) that showed that the PTSD Mean score decreased over time [from 32.98 (SD = 15.42) to 30.76 (SD = 15.42)].…”
Section: Resultsmentioning
confidence: 92%
“…Also, the Chinese version of IES-R (CIES-R) has shown valid and satisfactory psychometric properties in the Chinese context [Intrusion (Cronbach's α = 0.89), Avoidance (Cronbach's α = 0.85), and Hyperarousal (Cronbach's α = 0.83)] ( 103 , 104 ). Furthermore, IES-R has been used in numerous studies to measure the psychological impact of COVID-19-related experiences [e.g., ( 15 , 16 , 54 , 59 , 60 , 68 , 105 , 106 )].…”
Section: Methodsmentioning
confidence: 99%
“…The high prevalence of emotional distress in medical staff during the COVID-19 pandemic deserves great attention ( 15 – 19 ). Nurses are more prone to anxiety in the late stage of epidemic development ( 20 22 ). The relationship between the negative emotions and the comfort of the working environment is worthy of further study in the future.…”
Section: Discussionmentioning
confidence: 99%